Nilai-nilai Patriotisme dalam Novel Bila Malam Bertambah Malam Karya Putu Wijaya dan Implikasi dalam Pembelajaran Bahasa Indonesia di SMA - Muhammad Latif; Dewi Anggraini (ISLAMIKA, 2023)
At this time it can be observed that there are more striking differences in the spirit of the youth of the past and today. There has been a decline or deviation in morals which has caused today's youth to lose their spirit and spirit of independence so that there has been a decline in the values of patriotism that have occurred in all corners of the country. The purpose of this research is as follows. First, to describe the values of patriotism contained in Putu Wijaya's novel BMBM. Second, to describe the implications of the values of patriotism contained in Putu Wijaya's novel BMBM in teaching class XII high school novel texts. The research method used is content analysis. In this study the researcher himself acted as the main instrument. The research data analysis technique is adapted to the flow of qualitative data analysis. Putu Wijaya's novel When the Night Increases the Night found 15 values of patriotism. Each of the values of patriotism, namely 4 love of the motherland, 8 willing to sacrifice, 3 brave. Based on the results of the research, it was concluded that in Putu Wijaya's novel Bila Malam Lagi Malam, there are values of patriotism, namely an attitude of love for the motherland by having a spirit of responsibility, love for the symbol of the country, love for the teaching profession, a sense of indebtedness, support government programs and love for their students. The values of patriotism in Putu Wijaya's novel When the Night Increases in Night can be implicated in every lesson, outside of learning, in the school environment, in the community, and in the people around him. These values of patriotism can make everyone respect cultural, racial, ethnic and religious differences.